PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Darma, I Dewa Gede Ariandita; Sutrisna Dewi, Sayu Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p07, 2023)
The stock price is a very important factor and must be considered by investors in investing because the stock price shows the performance of the issuer. The movement of stock prices is in line with the performance of the issuer, if the issuer has better performance, the profits obtained and generated from business operations will be greater. The purpose of this study was to examine the effect of profitability and liquidity on stock prices with capital structure as an intervening variable. The population of this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample used was determined by purposive sampling method, and obtained a sample of 15 companies. The model analysis technique used is path analysis. The results of this study indicate that profitability and liquidity have a negative effect on capital structure. The second result that profitability has a positive effect on stock prices and liquidity has a negative effect on stock prices, and capital structure is not able to mediate profitability and liquidity on stock prices